Molecular simulation of transport through ordered porous channels - Chye, Joseph Chee Siong. (2010)
In this project, we have simulated the diffusion of a hard sphere fluid inside carbon nanotubes (CNT) of armchair and zig-zag configurations to investigate the transport properties in CNTs. Simulations were carried out using java-based modules that run on deterministic Molecular Dynamics (MD) to determine the atomistic properties of the fluid movement. The CNTs were varied from (4,4) to (10,10) configurations for the armchair and (4,0) to (10,0) for the zig-zag configurations. Simulation results showed an increase in diffusivity with an increment in CNT diameter which is determined by the configuration of the CNT. Comparison with literature showed that the results obtained were within acceptable limits and that the transport properties could also be affected by other factors such as fluid molecule orientation. Attempts to model real molecules like n-pentane and isopentane using hard sphere models were carried out, however results showed that usage of hard sphere model was only feasible for molecules with compact and branched structures while simulations of linear-chain molecules were inaccurate due to its elongated shape and orientation. Results obtained in this project are recommended to be used as points of reference as the modules used in the simulation resembles hard sphere fluid behavior and hence cannot be used to represent real gases, however the dimensions and parameters used are similar to the actual molecular properties and can be varied accordingly to simulate different configurations or compounds.